A Meta analysis on effect of auricular point sticking and pressing therapy in the treatment of hyperemesis gravidarum (耳穴贴压法治疗妊娠恶阻临床疗效的Meta分析) - TIAN Tian (田恬); XIE Wei (谢薇); DENG Yunyan (邓云燕); LI zhongqing (李忠琴); ZHANG yang (张杨); ZHAO Su (赵苏) (中西医结合护理)
Objective To evaluate the clinical effect of auricular point sticking and pressing therapy in the treatment of hyperemesis gravidarum. Methods Use of computer to search Cochrane, PubMed, China Knowledge Network Full Text Database (CNKI), VIP Database and Wanfang Database, to collect Randomized Controlled Trials (RCTs) about auricular point sticking and pressing therapy in the treatment of hyperemesis gravidarum were collected, and the quality of the included studies was evaluated according to the randomly hidden quality standard in Jadad scale. Meta analysis was performed by Rev man 5. 3 software. Results Five studies were included, including 359 patients with hyperemesis gravidarum. The results of meta-analysis showed that: ① The curative effect rate of auricular point sticking and pressing therapy was superior to the basic treatment group ［MD = 2. 42, 95% CI (2. 14, 5. 45), z = 5. 16, P < 0. 00001］. ② The total effective rate of auricular point sticking and pressing therapy group was superior to the basic treatment group ［MD = 5. 01, 95% CI (2. 495, - 10. 07), z = 4. 52, P < 0. 00001］. Conclusion Auricular point sticking and pressing therapy is better than basic therapy in the treatment of hyperemesis gravidarum. However, the mechanism of auricular plaster therapy is not clear and needs to be studied. (目的 评价耳穴贴压法治疗妊娠恶阻的临床效果。方法 通过计算机检索中国知网(CNKI)、维普数据库(VIP)、万方数据库(Wanfang Database)、PubMed及Cochrane library, 收集耳穴贴压法治疗妊娠恶阻的随机对照试验, 按照Jadad量表中随机隐藏的质量标准来评价所纳入研究的质量。采用Rev Man 5. 3软件进行Meta分析。结果 共纳入5篇研究, 包括359例妊娠恶阻患者。Meta分析结果显示: ①耳穴贴压组在治愈率上反应的疗效优于基础治疗组［MD=2. 42, 95%CI(2. 14, 5. 45), Z=5. 16, P＜0. 00001］。②耳穴贴压组在总有效率上反应的疗效优于基础治疗组［MD=5. 01, 95%CI(2. 495, -10. 07), Z=4. 52, P＜0. 00001］。结论 耳穴贴压法治疗妊娠恶阻优于单纯基础治疗, 但耳穴贴压法的起效机制尚未明确, 需有待研究。)